A Study of Oxidative Stress Markers when Using the Liposomal Antioxidant Complex - Pylypenko, D. M.; Gorbach, T. V.; Katsai, O. G.; Grigoryeva, A. S.; Krasnopolsky, Yu. M. (Hellenic Pharmaceutical Society, 2019)
The aim of the study was to create the complex liposomal preparation containing Coenzyme Q10 and Quercetin and learn its antioxidant activity. The liposomes were obtained the lipid film method followed by emulsification with PBS, extrusion and sterilizing filtration. The emulsion was lyophilized with lactose as a cryoprotectant. The ratio of Coenzyme Q10 and Quercetin in complex liposomal composition was 1:1. The particles size and the degree of inclusion were determined. Pharmacological study was carried out on Wistar line rats with experimental ischemic heart disease model. The samples of complex liposomal composition and monocompositions of Coenzyme Q10 and Quercetin were intravenously administered daily for 5 days at a dose of 10 mg/kg. Oxidative stress markers (levels of malondialdehyde, conjugated dienes, sulfhydryl groups, protein peroxidation, enzyme superoxide dismutase catalase and total antioxidant activity) were analyzed in blood serum and cardiac tissue of the rats. The obtained complex composition was characterized by a particle size of up to 220 nm and at least 90.0 % of the included Coenzyme Q10 and Quercetin. A decrease in the level of lipid oxidation products and an increase in the activity of antioxidant system using the complex liposomal preparation containing Coenzyme Q10 and Quercetin compared to its monocompositions in liposomal form were shown.
Keywords: oxidative stress; antioxidant activity; liposome; coenzyme Q10; quercetin